Fine mapping of RBG2, a quantitative trait locus for resistance to Burkholderia glumae, on rice chromosome 1 - Mizobuchi, Ritsuko (Mol Breed, 2015)
Bacterial grain rot (BGR), caused by the bacterial pathogen Burkholderia glumae, is a destructive disease of rice. At anthesis, rice panicles are attacked by the pathogen, and the infection causes unfilled or aborted grains, reducing grain yield and quality. Thus, increasing the level of BGR resistance is an important objective for rice breeding. A quantitative trait locus (QTL) on rice chromosome 1 that controls BGR resistance was previously detected in backcross inbred lines (BILs) derived from a cross between Kele, a resistant traditional lowland cultivar (indica) that originated in India, and Hitomebore, a susceptible modern lowland cultivar (temperate japonica) from Japan. Further genetic analyses using a BC(3)F(6) population derived from a cross between a resistant BIL (BC(2)F(5)) and Hitomebore confirmed that a QTL for BGR resistance was located on the long arm of chromosome 1. To define more precisely the chromosomal region underlying this QTL, we identified nine BC(2)F(6) plants in which recombination occurred near the QTL. Substitution mapping using homozygous recombinant and nonrecombinant plants demonstrated that the QTL, here designated as Resistance to Burkholderia glumae 2 (RBG2), was located in a 502-kb interval defined by simple sequence repeat markers RM1216 and RM11727. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s11032-015-0192-x) contains supplementary material, which is available to authorized users.